2019
DOI: 10.1590/1678-7757-2018-0744
|View full text |Cite
|
Sign up to set email alerts
|

The use of remote microphone systems in unilateral hearing loss: a preliminary study among Brazilian children and teenagers

Abstract: Due to the large number of individuals with Unilateral Hearing Loss (UHL) and the recommendation to use hearing assistive devices, studies are required to define possibilities of intervention for this population. Objective: To evaluate the performance of the Remote Microphone System (RMS) in children with UHL. Methodology: Prospective clinical study with a convenience sample. Eleven children (mean age of 9.2 years) with severe and profound sensorineural UHL, hearing aid users and enrolled in regular schools pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Until recently, the effects of UHL in children have been understudied, and assumed to be minimal (44). For example, children with UHL in the United Kingdom are not routinely funded to have a remote microphone system (RMS), a wireless microphone system that transmits sound from a talker to the receiver's ear (28), even though use of RMS has been shown to improve performance in sustained auditory attention ability (45).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the effects of UHL in children have been understudied, and assumed to be minimal (44). For example, children with UHL in the United Kingdom are not routinely funded to have a remote microphone system (RMS), a wireless microphone system that transmits sound from a talker to the receiver's ear (28), even though use of RMS has been shown to improve performance in sustained auditory attention ability (45).…”
Section: Discussionmentioning
confidence: 99%
“…The use of a RM has been reported to be associated with improvements in various hearing-impaired populations [30,59,60]. Moreover, RM systems are reported to have the advantage of not eliminating the head shadow effect, avoiding the significant reduction in speech perception when the signal comes from the better hearing side and the noise contralaterally (SbNw), which is typical of CROS systems [60].…”
Section: Discussionmentioning
confidence: 99%
“…Access to critical speech information is negatively affected, even at small distances typical of classroom environments [Leavitt and Flexer, 1991], and compounded by the presence of competing noise. Further, previous studies have demonstrated that listening abilities are compromised in classroom environments even in mild and unilateral HL [Hawkins, 1984;Ruscetta et al, 2005;Noh and Park, 2012] and aided listening [Hawkins, 1984;Smaldino and Crandell, 2000;Lewis et al, 2004;Mondelli et al, 2019;Snapp et al, 2020].…”
Section: Introductionmentioning
confidence: 95%